Experimental study of the spray, combustion, and emission performance of a diesel engine with high n-pentanol blending ratios. (15th August 2019) - Pan, Mingzhang; Huang, Rong; Liao, Jinyang; Jia, Chaojie; Zhou, Xiaorong; Huang, Haozhong; Huang, Xiaodong
Highlights: Optical diagnostic method was used to analyze n -pentanol/diesel spray process. Blends of n -pentanol/diesel showed better atomization characteristics than diesel. The addition of 50% n -pentanol to diesel can reduce two-thirds of soot emissions. Adding 50% n -pentanol to diesel significantly increased the BSFC and HC emissions. Abstract: n -Pentanol exhibits some advantageous fuel properties, such as a higher energy density, lubricity, viscosity, and low hygroscopicity, when compared to short-chain alcohols. It is miscible with pure diesel in large proportions and burns directly on diesel engines. Therefore, n -pentanol is considered to be a promising diesel fuel additive. However, the differences between the chemical and physical properties of n -pentanol and commercial diesel affect the spray, combustion, and emissions performance of commercial diesel engines. In this study, visualization and engine experimental test methods were used to study the spray, combustion, and emissions performance of diesel/ n -pentanol mixtures. The results showed that the atomization characteristics of diesel/ n -pentanol mixtures were better than those of diesel. As the engine load increased, the maximum in-cylinder pressure and heat release rate increased. The brake specific fuel consumption (BSFC), nitrogen oxide (NOX ), hydrocarbons (HC), and carbon monoxide (CO) emissions decreased, but soot emissions increased. Compared to diesel fuel, adding n -pentanol to pure diesel resulted in a decrease in soot emissions, while the BSFC, HC, and NOX emissions increased. Upon adding 50% n -pentanol to pure diesel (P50), the soot emissions decreased by up to 77.15% and the brake thermal efficiency (BTE) decreased by 1.86%. In summary, P50 could be burned directly on the diesel engine without any modifications, which can significantly reduce soot emissions; in this case, the BTE experienced only a slight decrease.